Goal-based decision making : an interpersonal model - Slade, Stephen (L. Erlbaum, 1994)
This work presents a goal-based model of decision making in which the relative priorities of goals drive the decision process -- a psychological alternative to traditional decision analysis. Building on the work of Schank and Abelson, the author uses goals as the basis for a model of interpersonal relations which permits decisions to incorporate personal and adopted goals in a uniform manner. The theory is modelled on the VOTE computer program which simulates Congressional roll-call voting decisions. The VOTE program expands traditional decision making and simulation models by provid.